Assessing students’ perception of the surgical theatre educational environment of a private medical college in Pakistan - Tayaba Sarfraz; Syed Muhammad Azfar; Syeda Rubaba Azim; Mutayyaba Majeed (Journal of University Medical & Dental College, 2024)
ABSTRACT BACKGROUND & OBJECTIVE: The learning environment is a crucial part of any educational institute. It should be ensured that the learning environment is facilitating the learning process. This study aims to assess undergraduate medical students’ perception of the learning environment of surgical theater. METHODOLOGY: This was a cross-sectional study done at Liaquat College of Medicine and Dentistry (LCMD) a private medical college in Karachi. Data was collected from final-year students, who attended surgical rotation using a pre-validated questionnaire “Surgical Theatre Educational Environment Measure (STEEM)” and analyzed using SPSS version 23.0. RESULTS: Eighty-eight (n=88) out of a hundred participants have completed the given questionnaire. Most of the students (64.26%) were overall satisfied with the learning environment in the surgical theatre of the institute (p-value=0.083). Male students were found more satisfied with the learning environment as compared to their female counterparts. The overall Cronbach alpha of STEEM was found 0.75. CONCLUSION: The outcomes of this study revealed that most of the students of LCMD had positive perceptions of instruction and training in surgical theatre.